2006
DOI: 10.1158/0008-5472.can-05-3387
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Endothelial Cells Express Epidermal Growth Factor Receptor (EGFR) but not ErbB3 and Are Responsive to EGF and to EGFR Kinase Inhibitors

Abstract: Epidermal growth factor (EGF) receptor family members are expressed by tumor cells and contribute to tumor progression. The expression and activity of EGF receptors in endothelial cells are less well characterized. Analysis of tumor-derived endothelial cells showed that they express EGFR, ErbB2, and ErbB4, whereas their normal counterparts express ErbB2, ErbB3, and ErbB4. The gain in expression of EGFR and the loss of ErbB3 expression in tumor vasculature was also observed in vivo. As a consequence of their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
140
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 33 publications
5
140
2
1
Order By: Relevance
“…These comparative studies, which focused solely on differences in canonical biochemical signaling pathways, revealed that tumor CE cells exhibit altered growth factor signaling arising from differential expression of important growth factor receptors (30,32). Here, we show that tumor CE cells also exhibit aberrant Rho-mediated mechanosensitivity to physical cues from the ECM that are equally important for control of vascular development, and thus, these findings may have important implications for abnormal tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…These comparative studies, which focused solely on differences in canonical biochemical signaling pathways, revealed that tumor CE cells exhibit altered growth factor signaling arising from differential expression of important growth factor receptors (30,32). Here, we show that tumor CE cells also exhibit aberrant Rho-mediated mechanosensitivity to physical cues from the ECM that are equally important for control of vascular development, and thus, these findings may have important implications for abnormal tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…Tumor endothelial cells express EGFR and are responsive to pro-angiogenic stimuli mediated by EGF. 25 Here, we report that EGF induces Bcl-x L expression in primary endothelial cells, and has a potent angiogenic effect in vitro. Endothelial cells transduced with shRNA-Bcl-x L were significantly less responsive to the pro-angiogenic signal mediated by EGF than endothelial cells transduced with an empty vector control lentivirus.…”
Section: Discussionmentioning
confidence: 78%
“…EGFR has been shown to be expressed in tumor endothelial cells, while undetectable in their normal counterparts, and plays a role in their proliferative phenotype (66). In addition, MT1-MMP is also expressed in angiogenic endothelial cells and is well known to be an important regulator of angiogenesis (3,(11)(12)(13)67).…”
Section: Mt1-mmp Induces Migration Via Egfr Transactivation Mol Cancementioning
confidence: 99%